0901 Dose-Response Relationship Between Insufficient Sleep and Mental Health Symptoms in Collegiate Student Athletes and Non-Athletes. (12th April 2019) - Ramsey, Thea; Athey, Amy; Ellis, Jason; Tubbs, Andrew; Turner, Robert; Killgore, William D S; Warlick, Chloe; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: Previous studies have shown that sleep quality is related to mental health. Fewer studies have examined insufficient sleep, especially among student athletes, who frequently experience short sleep duration. Methods: Data were aggregated from the 2011-2014 waves of the National College Health Assessment, conducted by the American College Health Association. These data included N=110, 496 individuals who provided complete data, including N=8, 462 varsity athletes. Insufficient sleep was assessed as number of nights students did not "get enough sleep so that you felt rested when you woke up, " coded as 0-7. Mental health symptoms were assessed as presence in the past 30 days of feelings of hopelessness, feeling overwhelmed, exhaustion, loneliness, sadness/depressed mood, difficulty functioning, anxiety, anger, desire to self-harm, suicide ideation. Covariates included age, sex, race/ethnicity, and survey year. Logistic regression models examined the complete sample and interaction terms for sleep-x-athlete status. Additional models included controls for insomnia and depressed mood. Results: In adjusted models, insufficient sleep was associated with all mental health variables; when insufficient sleep was treated as categorical (reference=0), a dose-response relationship was seen. Thus, subsequent analyses examined linear trends. More nights of insufficient sleep was associated with greater likelihood of hopelessness (OR=1.24; p<0.0005), feeling overwhelmed (OR=1.23; p<0.0005), exhaustion (OR=1.29; p<0.0005), loneliness (OR=1.19; p<0.0005), depressed mood (OR=1.21; p<0.0005), functional problems (OR=1.28; p<0.0005), anxiety (OR=1.25; p<0.0005), anger (OR=1.24; p<0.0005), desire to self-harm (OR=1.25; p<0.0005), and suicide ideation (OR=1.28; p<0.0005). Sleep-x-athlete interactions were significant for all variables (p<0.0005), but stratified analyses were nominally similar. When insomnia and depressed mood were entered as covariates, results were attenuated but remained significant (all p<0.0005). Conclusion: There is a dose-response relationship between insufficient sleep and many domains of mental health in collegiate students (athletes and non-athletes), and this relationship is not accounted for by insomnia and/or depressed mood alone. Mental health efforts on campuses should focus on achieving sufficient sleep. Support (If Any): R01MD011600, NCAA Innovations Grant